eMagRes 2014
DOI: 10.1002/9780470034590.emrstm1354
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of Eye Lens Crystallins

Abstract: The crystallins of the eye lens are highly stable, soluble proteins that generate the refractive index gradient of the lens. In their native context, the crystallins form large soluble oligomers; a loss in solubility due to mutation, UV light damage, or chemical modification results in cataract. There are two broad classes of ubiquitous crystallin proteins; βγ -crystallins, which are purely structural, and the α-crystallins, which additionally play a chaperone role, maintaining solubility of compromised protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Therefore, many structural studies have been performed using solution‐state NMR, as reviewed in ref. [45] and discussed for several cataract‐related variants in Section 5. In addition to providing ensembles of structures in solution, this method enables the investigation of dynamics over a wide range of timescales and to detect rare conformational states [46–48] .…”
Section: Biophysical Techniques For Studying Crystallinsmentioning
confidence: 99%
“…Therefore, many structural studies have been performed using solution‐state NMR, as reviewed in ref. [45] and discussed for several cataract‐related variants in Section 5. In addition to providing ensembles of structures in solution, this method enables the investigation of dynamics over a wide range of timescales and to detect rare conformational states [46–48] .…”
Section: Biophysical Techniques For Studying Crystallinsmentioning
confidence: 99%
“…Solving the structures of α-crystallins in biologically relevant complexes is a challenging endeavor. Their dynamic and polydisperse nature makes them particularly suitable for NMR (see the sidebar titled NMR Assignments and Structure Determination) (53,54), and in many cases…”
Section: Solution Nmrmentioning
confidence: 99%
“…Point mutations are frequently assumed to have only a very local effect on protein structure; our work and that of other groups have indicated that this is often not the case for crystallins. 35 As discussed in the previous section, the relatively minor conformational change caused by the G18V mutation nevertheless propagates down the polypeptide chain through more than half of the N-terminal domain. 30 In collaboration (A) Thermal unfolding data for variants of human γS-crystallin: γS-WT (green), γS-G18V (light blue), γS-G106V (magenta), and γS-G106V/M108R (purple).…”
Section: Clients By the Holdase Chaperone αB-crystallinmentioning
confidence: 87%